Konsep Tauhid Menurut Abdul Karim Amrullah dan Implikasinya terhadap Tujuan Pendidikan Islam - Ichsan Saputro (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2016)
Today, the translation of the concept of tauhid, often only beinterpreted as a form of oneness of Allah SWT. Whereas conception of tauhidcould be articulated more extensive and comprehensive. One of them is theconcept put forward by Dr. H. Abdul Karim Amrullah contained in an articleentitled “Hanya Allah” written around 1943. He established a school of thestudy of Islam begins with small classes at Surau Jembatan Besi PadangPanjang. Education in surau evolved into Sumatra Thawalib . At that time,Thawalib Sumatra Padang Panjang is organized as a modern educationalinstitution with a structured curriculum. But he also did not separate thecommunity life: social, economic, and politic, so that graduates are notawkward in the face of society. This educational products that can bereflected in the present, so that the building concept of aqidah (tauhid) isnot only interpreted as the oneness of Allah SWT. as the only God is worthyof worship. But it also brings logical consequence of human proclamationas khalifatullah fil ardh (vicegerent on earth) that is ready for the welfare ofthe earth and its contents.